An Analysis of Types of Setting in Literature to Construct Plot in Sherlock Holmes Movie - Darmayanti, Ni Putu Eka; Jayantini , I G. A. Sri Rwa; Juniartha , I Wayan (Journal of Language and Applied Linguistics, 2024)
This study aimed to analyze the types of setting and to discuss of how the setting constructs the plot. The data of this study were taken from Sherlock Holmes movie. The theories used in this study are theory proposed by Kenney (1966) to determine the setting of the movie and the theory proposed by Klarer (2004) to analyze the plot construction. Based on Kenney’s theory, setting can be divided into two types, namely: neutral setting and spiritual setting. The findings of this study related to the neutral setting showed there are 3 types such as setting of place was found 20 (62,5%), setting of time was found 4 (12,5%) and setting of environment was found 6 (18,75%). As for spiritual setting, it was found only 2 (6,25%). Furthermore, based on the analysis of how the setting constructs the plot in the movie, it can be concluded that the data for the construction of plot there are 4 types which are exposition was found 1 (10%), complication was found 4 (40%), climax was found 4 (40%) and resolution was found 1 (10%).